Penyuluhan Metode Kontrasepsi Jangka Panjang (MKJP) dan Pemasangan Kontrasepsi Jenis Intra Uteri Devaice dan Implan: Penyuluhan Metode Kontrasepsi Jangka Panjang (MKJP) dan Pemasangan Kontrasepsi Jenis Intra Uteri Devaice dan Implan - Sri Dinengsih; Eka Oktavia (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
The Family Planning Program is an integral and inseparable part of the national development program, which seeks to create economic, spiritual and social integration. The Covid-19 pandemic has resulted in delays in family planning services, especially for MKJP (long-term birth control method) family planning services and restrictions on visits to Health facilities, for example hospitals and community health centers, estimated global impact of Covid-19 on reproductive health due to lockdown for 6 months. 47 million women in 114 low and middle income countries are projected to not have access to modern contraception. If there is a disruption in the availability of modern contraceptive services, it will result in 7 million unwanted pregnancies. This condition has an impact on the continuity of public health services, including family planning and reproductive health services. In this pandemic condition, WUS with 4T are expected not to become pregnant, so health workers need to ensure they continue to use contraception. Community service aims to increase the level of knowledge about MKJP among women of childbearing age (WUS) so that WUS will use MKJP (IUD & Implants). The subjects of this activity were 12 women of childbearing age at TPMB